Estimation of Phenotypic and Genotypic Correlation Analysis in F3 Populations of Bread Wheat Genotypes - Akbar Ali; Mansoor Javed Momand; Muhammad Ali; Saeed Ur Rahman; Salman Abbas (Turkish Journal of Agriculture: Food Science and Technology)
Wheat is one of the most important crops all over the world in terms of yield, production, consumption, cultivation, and adoptability. Wheat genotypes exhibiting different yield associated traits which influence each other in many ways. Therefor genotypic and phenotypic correlations are the breeder’s utmost priority to know about the inter-relationship between two or more traits which may be either directly influencing each other in a positive direction or indirectly swaying each other in a negative direction in breeding programs. To find out phenotypic and genotypic correlations among different productive traits, this study was designed at the research area of The Department of Plant Breeding and Genetics, The University of Agriculture, Peshawar, during 2022-23. The experiment was carried out by using 27 wheat genotypes comprising of nine parents and 18 F3 populations evaluated in RCB design with three replications. Overall the study exhibited that kernel yield plant-1, which is one of the most yield contributing trait, was significantly correlated with thousand-kernel weights, tillers plant-1and biomass yield, along some other yield contributing traits. The parental genotype, Janbaz, and cross combinations Watan × AUP-5008, Pirsabak-2005 × AUP-5008, Saleem-2000 × Janbaz and Watan × Tatara were the most promising genotypes for most of quantitative traits and; hence are recommended to be evaluated in further breeding schemes. Both phenotypic and genotypic correlation study exhibited that kernel yield spike-1 was significant and positively associated with plant height, tillers plant-1, thousand-kernel weight and biomass yield. Based on correlations, yield, and production the parental genotype, Janbaz, and F3 combinations Watan × AUP-5008, Pirsabak-2005 × AUP-5008, Saleem-2000 × Janbaz and Watan × Tatara were the most promising genotypes for most of the quantitative traits, which can be incorporated in further breeding program.